The Effect of User Participation in Satisfaction: Beyciler After-Earthquake Houses in Düzce - Erinsel Önder, Deniz; Köseoğlu, Emine; Bilen, Ömer; Der, Venhar (İstanbul Teknik Üniversitesi, 2010)
Natural disasters that have occurred in recent years in Turkey have caused loss of property as well as deaths. Thus, they have necessitated the immediate construction of much housing. Many users neither adopted this housing, nor settled into it. The aim of this paper is to explore how user participation in design and construction process affects user satisfaction. As part of the study, a questionnaire was run (n=100) in a mass housing area with 168 units in Düzce, which was realized by the participation of the users after the 1999 Marmara earthquakes. The results of the questionnaire were evaluated on SPSS (Statistical Package for Social Sciences) using one sample t-test, Mann-Whitney U test and chi-square test. Results showed that, in terms of houses‘ exterior spaces and general characteristics, there is no significant difference between the residents who participated to design and construction process and who did not. As for psychological needs and quality of interior spaces, the degree of satisfaction of the users that participated in the design and construction process was found higher than the ones that did not participated. In general, the study revealed that not only were the users pleased to have been involved in the process, but they were also satisfied with their accommodation.
Keywords: Residential Quality; User Satisfaction; Participatory Design